Confinement of reinforced concrete columns with glass fiber reinforced cementitious matrix jackets. (1st September 2020) - Faleschini, Flora; Zanini, Mariano Angelo; Hofer, Lorenzo; Toska, Klajdi; De Domenico, Dario; Pellegrino, Carlo
Highlights: RC columns strengthened with E-glass fiber reinforced cementitious matrix (GFRCM). The variables of the experiment are column cross-section and stirrups spacing. GFRCM jackets enhance confined compressive strength and axial strain capacity. Strength degradation is improved when GFRCM is used. Stirrup and fiber exploitation is experimentally evaluated. Abstract: This paper shows the results of an experimental campaign aimed at testing eight reinforced concrete (RC) columns, four of them being confined through E-glass fiber reinforced cementitious matrix (GFRCM) and four representing the bare specimens. The variables analyzed in this work are: the geometry of column cross-section (circular or square); two stirrups spacing values; the presence or not of the FRCM jacket, which was realized through two layers of fibers. The experimental behavior was characterized in terms of cracking pattern, axial stress-strain response (i.e., strength gain and ductility), and hoop strains development. Particularly, both strains in the GFRCM-jacket and in the inner steel stirrups were monitored during the test. Results in terms of fiber exploitation ratio are also compared with recent results obtained for carbon FRCM (CFRCM) jackets applied to RC columns, characterized by the same geometry.